The Barriers Related to the Implementation of the Circular Economy in Poland - Raftowicz, Magdalena; Ochman, Małgorzata (Bariery implementacji gospodarki o obiegu zamkniętym w Polsce, 2024)
Aim: The main goal of the research was to identify barriers that arise on the path to implementing a circular economy in Poland and to propose solutions to reduce these barriers. Methodology: The research was conducted based on a critical analysis of the literature on the subject and survey research among companies engaged in environmental/waste-related activities, as well as among households. Results: The research results indicated that there is a completely different approach among companies and households regarding the barriers to implementing a circular economy. Implications and recommendations: A practical aspect of the discussed issues is the possibility of utilising the research results by the Ministry of Climate and Environment to shape policies in line with the European Green Deal. In order to overcome these barriers, institutional support is essential, both in financial, technological, legal, and educational aspects. Originality/value: Filling a research gap in the literature regarding the identification of barriers arising on the path to implementing a circular economy based on the example of Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 35-50
Keywords: circular economy; barriers; Poland; gospodarka w obiegu zamkniętym; bariery; Polska